EVIDENCE-BASED PRACTICE AS A PART OF KNOWLEDGE MANAGEMENT IN NURSING - Špačková, Iva; Holá, Jana (Trauner Verlag, 2016)
The aim of this paper is to show the use of evidence-based practice (EBP) as a part of knowledge management in health care, with a focus on Czech nursing. The conditions of the knowledge management functioning in health care are generally described in the opening chapter of the text. Furthermore, the paper deals with the explanation of the concept of EBP and refers to some problems of EBP implementation in Czech nursing practice. The final part of the text focuses on the theoretical preparation of students of the medical universities to manage this problem in the clinical practice, including a summary of the results of research on the extent of teaching EBP at Czech universities providing education in nursing.
PRAXE ZALOŽENÁ NA DŮKAZECH JAKO SOUČÁST ZNALOSTNÍHO MANAGEMENTU V OŠETŘOVATELSTVÍ
Keywords: Knowledge management; evidence-based practice; health care; nursing; Znalostní management; praxe založená na důkazech; zdravotnictví; ošetřovatelství